PENGARUH STACK BERBAHAN ORGANIK TERHADAP PERUBAHAN SUHU PADA SISTEM PENDINGIN TERMOAKUSTIK GELOMBANG BERDIRI DAN GELOMBANG BERJALAN - HIDAYAH, QONITATUL ([Yogyakarta] : Universitas Gadjah Mada, 2015)
It has been researched to determine the influence of organic stack on the temperature changes in standing wave and traveling wave of thermoacoustic refrigerator system. This study used three types of organic material stack, namely sponge gourd (luffa acutangula), rice trunks, and pineapple fibers. On standing wave and traveling wave of thermoacoustic refrigerator, the resonance frequency have shifted as consequence of existence of the arbitrarily stack. By thermoacoustic system, as a result is the decreasing temperature on the both reservoirs (hot and cool reservoirs). For pineapple fiber stack, the decreasing temperature is achieved around (12,6 ± 0,1) oC for the optimum length of stack is around 7 cm on the optimum power of 60 W. Using the sponge gourd and the rice trunk which have the same optimum length (8 cm), the decrease temperature is around (11,7 ± 0,1) oC and (8,1 ± 0,1) oC respectively on the optimum power of 60 W. On the traveling wave thermoacoustic refrigerator, when using the best of stack materials and the optimum length of stack which is used in standing wave thermoacoustic system, the temperature decrease is achieved at (8,1 ± 0,1) oC on the optimum power of 50 W.